Manifestasi Teologi Tanah Hassan Hanafi Dalam Gerakan Reclaiming Petani Di Rotorejo-Kruwuk Blitar - Afifudin, Ridho (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract This paper discusses the movement of farmer groups in Blitar in fighting for their rights to plantation land. The land is the company's land that has expired its contract (ex-HGU), so based on government regulations and existing laws, the position of the land may be claimed by residents. But the struggle of the farmers was not as smooth as expected. Various upheaval arose in the process. From this problem, the author sees this problem from the perspective of Hassan Hanafi’s concept of theology. Hanafi explained how human faith became the spirit of the movement to fight for justice. There are two principles stated; First, the principle of needs and benefits, is who most needs access to the land along with the large benefits that will be received. Second, the principle of agreement and understanding; This principle concerns the process of negotiation (deliberation) between the two parties, especially in terms of compensation (ta'widh) if there is a party harmed. Keywords: Teologi, Hassan Hanafi, Gerakan Petani. Abstrak Artikel ini membahas pergerakan kelompok tani di Blitar dalam memperjuangkan hak mereka atas tanah perkebunan. Tanah tersebut adalah tanah perusahaan yang telah habis masa kontraknya (ex-HGU), jadi berdasarkan peraturan pemerintah dan undang-undang yang ada, posisi tanah tersebut dapat diklaim oleh penduduk. Namun perjuangan para petani itu tidak semulus yang diharapkan. Berbagai pergolakan muncul dalam prosesnya. Dari masalah ini, penulis melihat masalah ini dalam perspektif konsep teologi Hassan Hanafi. Seperti yang Hanafi jelaskan tentang bagaimana iman manusia menjadi semangat gerakan untuk memperjuangkan keadilan. Ada dua prinsip yang dinyatakan; Pertama, prinsip kebutuhan dan manfaat, adalah siapa yang paling membutuhkan akses ke tanah bersama dengan manfaat besar yang akan diterima. Kedua, prinsip kesepakatan dan pemahaman; Prinsip ini menyangkut proses negosiasi (musyawarah) antara kedua pihak, terutama dalam hal kompensasi (ta'widh) jika ada pihak yang dirugikan. Kata Kunci: Teologi, Hassan Hanafi, Gerakan Petani.